Hybrid structure of cobalt monoxide nanowire @ nickel hydroxidenitrate nanoflake aligned on nickel foam for high-rate supercapacitor - Zhang, Hua (2012)
A new hybrid nanostructure of porous cobalt monoxide nanowire @